From demyelination to neurodegeneration in multiple sclerosis: reassessing the role of visual evoked potential P100-N145 amplitudes: a missing piece of the puzzle? - Kaya Tutar, Nurhan; Kale, Nilufer (Frontiers in Neurology, 2025)
BackgroundMultiple sclerosis (MS) is a chronic demyelinating disease with a heterogeneous clinical course, making long-term disability prediction challenging. Visual evoked potentials (VEPs), particularly amplitude-based parameters, may serve as sensitive biomarkers of neurodegeneration and functional decline undetected by conventional clinical measures.ObjectiveTo assess the relationship between longitudinal changes in P100–N145 amplitude and concurrent Expanded Disability Status Scale (EDSS) changes in relapsing–remitting MS (RRMS) and the relative utility of baseline and longitudinal VEP parameters in representing disability status.MethodsIn this retrospective cohort study, 45 MS patients (90 eyes) with available VEP and EDSS data were followed for a median period of 48 months. The primary endpoints were (1) change in EDSS score over time and (2) EDSS progression, defined as any increase in EDSS score from baseline to follow-up. Generalized estimating equations (GEE) and logistic regression were used to investigate the relationships between the VEP parameters at baseline and follow-up and EDSS progression, accounting for inter-eye correlation; partial correlation analysis assessed amplitude–EDSS change associations, controlling for age.ResultsEDSS progression was observed in 17.8% of patients. A longitudinal decrease in P100–N145 amplitude from baseline to follow-up was significantly associated with EDSS progression (OR: 1.511, 95% CI, p < 0.001). In addition, partial correlation analysis adjusting for age revealed a significant negative association between the difference in P100–N145 amplitude and EDSS difference (defined as baseline minus follow-up) in both eyes (right eye: r = −0.339, p = 0.024; left eye: r = −0.406, p = 0.006). In contrast, the changes in P100 latency and N75–P100 amplitude did not correlate significantly with EDSS worsening. Baseline VEP parameters, including P100 latency, N75–P100, and P100–N145 amplitudes, did not predict EDSS progression or change over time (all p > 0.05).ConclusionOur results demonstrate that a reduction in P100–N145 amplitude over time is associated with worsening disability in RRMS. This suggests that the P100–N145 may be an underestimated marker of progressive functional deterioration in RRMS.